The Influence of Beauty Influencers, Brand Awareness, and Word of Mouth on the Purchase Decision of Skintific Beauty Products Among the People of Marendal I Village, Deli Serdang - Nurul Habibah; Yayuk Yuliana; Mhd Hilman Fikri; Mhd Dani Habra (Digital Innovation : International Journal of Management, 2026)
This research aims to determine the Influence of Beauty Influencers, Brand Awareness, and Word of Mouth on the Purchase Decision of Skintific Beauty Products Among the Community of Desa Marendal I Deli Serdang. In this study, the data collection technique used a random sampling method, with a sample of 97 respondents. All analyses in this research were assisted by SPSS 25.0 software. The data analysis techniques involved classical assumption tests, multiple linear regression analysis, and hypothesis testing. Based on the t-test conducted, the results showed that the Sig. value for the Beauty Influencer variable was 0.00 < 0.05, and the t-calculated value > t-table (6.871 > 1.661). Thus, it can be concluded that the Beauty Influencer variable has a positive and significant influence on the Purchase Decision variable. Furthermore, the Sig. value for the Brand Awareness variable was 0.00 < 0.05, and the t-calculated value > t-table (3.881 > 1.661). Thus, it can be concluded that the Brand Awareness variable has a significant influence on the Purchase Decision variable. Next, the Sig. value for the Word of Mouth variable was 0.047 < 0.05, indicating a significant influence on the Purchase Decision variable. From the data, the t-calculated value > t-table (1.786 > 1.661). Thus, it can be stated that the Word of Mouth variable has a positive and significant influence on the Purchase Decision variable. The F-test results show that Beauty Influencers, Brand Awareness, and Word of Mouth simultaneously influence the purchase decision of Skintific Beauty Products Among the Community of Desa Marendal I Deli Serdang, with the F-calculated value (49.633) > F-table (2.701), and a significance value of 0.000 < 0.05. The adjusted coefficient of determination (R Square) value is 0.616, meaning that 61.6% of the dependent variable can be explained by the independent variables, while the remaining 38.4% is explained by other variables outside those studied.